Transformasi Digital sebagai Solusi Preventif dalam Menjawab Tantangan Eksistensi Kesenian Bantengan Sumberputih di Era 4.0 - Rizal, Maulfi Syaiful; Rohman, Muh. Fatoni; Zakiyah, Millatuz; Wijayanti, Jamila; Ainurohma, Intan; Azzahra, Ayshaputri Raihana; Setyabudi, Fiona Benita; Falianty, Donna Zavira (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2025)
Bantengan, as one of the cultural heritages of Sumberputih Village, Wajak District, Malang Regency, faces serious challenges in the digital era due to the declining interest of the younger generation and the lack of documentation and promotion. This study aims to provide preventive solutions through digital transformation programs as part of Community Service activities. The research employed a qualitative method with a limited ethnographic approach, including literature review, observation, and interviews with Bantengan art practitioners. The findings show that digital transformation can be realized through several innovative products, namely the Suarasa Budaya podcast, the Langgam Sumberputih website, the Warisan Budaya Lereng Semeru e-book, and the Denyut Bantengan di Jantung Sumberputih documentary video. These four strategies complement each other in documenting, promoting, and educating the public about the cultural values of Bantengan. Thus, digitalization not only expands its promotion reach to national and international levels but also serves as a medium for empowerment and preservation of local culture to remain relevant and sustainable amid globalization.